Table of Content - - (Journal of Risk and Crisis Management, 2025)
:Table of Content• The Role of Strategic Management in Dealing with Risks Facing Companies: An Analytical Study in the Kingdom of Saudi Arabia – 2025Dr. Hanan Abdullah Natheer• The Role of Financial Risk Management in Promoting Sustainable Development: An applied study on Saudi sports clubs 2025Co-Prof. Noureldaim Eltayeb Yousif Elhag• An Intelligent Model for Predicting and Preventing Overcrowding Incidents in Holy Sites  Using Artificial Intelligence TechnologiesMr. Abdulrahman Abdulmatlob Alsulami
Keywords: Journal of Risk and Crisis Management